Compósito Nb-Cu obtido por ação mecânica e sinterização - comportamento físico, térmico e elétrico - Rotta, Maycon (2005)
The current demand for materials presenting better and peculiar characteristics has stimulated the new matrix development and new obtaining process of such new materials. It is usual the development of composites that combine high electrical conductivity from some elements with elements having high mechanical resistance compared to that for FCC structure found in Cr, W, Ta, Nb, Mo and V, owing to enhance the strength of particles of the composites. Among these composites, the Cu-Nb has shown good mechanical properties. However, the inversion of the metallic matrix with Nb being the matrix and Cu being the reinforcing less exploited. Thus, this work proposes the obtaining of the Cu-Nb composite using initially the Mechanical Alloying technique and after that the usage of sintering process. In order to study the influence of milling time (8, 16, 24 and 32 h) and the amount of reinforcement added to Nb in the composite microstructure, several techniques were applied such as X-ray diffraction (XRD) scanning electronic microscopy (SEM). These analyses allowed studying the morphology, crystalline degree and the interaction between the components in the composite Nb1-x-Cux (x = 5, 10, 15, 20% of Cu in fractional volume). The final composites were characterized after the sintering process and the mass density, thermal diffusivity, specific heat, thermal conductivity and electrical resistivity were obtained. SEM technique was also utilized in the analysis of the sintered samples. The results showed that the amount of reinforcement presents great influence in the final composite, since the small amount of Cu added to Nb did not allow the complete interaction between matrix and reinforcement with respect to milling process. This fact is a problem in the sinterability, which severely influences the final microstructure behavior as well as the densification, reflecting strongly in the thermal and electrical properties of this composite.